Next-generation Sequencing Reveals Recurrent Somatic Mutations in Small Cell Neuroendocrine Carcinoma of the Uterine Cervix. (June 2018) - Xing, Deyin; Zheng, Gang; Schoolmeester, John Kenneth; Li, Zaibo; Pallavajjala, Aparna; Haley, Lisa; Conner, Michael G.; Vang, Russell; Hung, Chien-Fu; Wu, Tzyy-Choou; Ronnett, Brigitte M.
Abstract : Small cell neuroendocrine carcinoma (SCNEC) of the uterine cervix is a rare but extremely aggressive tumor. While high-risk human papillomavirus (HPV) is involved at an early stage of oncogenesis in many tumors, additional driving events have been postulated to facilitate the progression of SCNECs. Identification of oncogenic drivers could guide targeted therapy of this neoplasm. Clinicopathologic features of 10 cervical SCNECs are reported. Analyses included immunohistochemical evaluation of p16, p53, synaptophysin, and chromogranin expression; in situ hybridizations and polymerase chain reaction for high-risk HPV and/or HPV 18; and next-generation sequencing based on a 637-gene panel. The patients ranged in age from 28 to 68 years (mean, 45.6 y; median, 40.5 y). All tumors had diffuse p16 and synaptophysin expression. All but 1 tumor was positive for chromogranin (extent of staining ranged from focal to diffuse). HPV 18 was detected in 6 tumors and HPV 35 in 1 tumor. At least 1 driver mutation was detected in 8 tumors. Four cases harbored TP53 somatic mutations, 3 of which correlated with an aberrant p53 staining pattern. Four PIK3CA mutations (p.G106A, p.N345T, p.E545K, and p.E545D) were detected in 3 tumors, 2 of which also harbored TP53 mutations. Oncogenic driver mutations involving KRAS, Erbb2, c-Myc, NOTCH1, BCL6, or NCOA3 were detected in 4 tumors. Mutations in caretaker tumor suppressors PTEN, RB1, BRCA1, BRCA2, and ARID1B were also identified in 4 tumors that commonly coharbored activating oncogenic mutations. Targeted next-generation gene sequencing identified genetic alterations involving the MAPK, PI3K/AKT/mTOR, and TP53/BRCA pathways in SCNECs. The presence of genetic alterations that are amenable to targeted therapy in SCNECs offers the potential for individualized management strategies for treatment of this aggressive tumor. Abstract : Supplemental Digital Content is available in the text.